2017
DOI: 10.1007/8904_2017_37
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Neuropathy, Episodic Rhabdomyolysis, and Hypoparathyroidism in a Patient with Mitochondrial Trifunctional Protein Deficiency

Abstract: A combination of unexplained peripheral neuropathy, hypoparathyroidism, and the inability to cope with metabolic stress could point to a rare inborn error of metabolism, such as mitochondrial trifunctional protein (MTP) deficiency.Here, we describe a 20-year-old woman who was known since childhood with axonal motor sensory polyneuropathy of unknown origin. She presented with progressive dyspnoea, and increased muscle weakness, preceded by 6 days of fever, vomiting, and diarrhoea. Laboratory testing showed rhab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…However, in the literature, late-onset neuromuscular MTPD with outcome of dietary treatment only accounted for a small portion of this subtype. A possible reason is that adult patients showed poor compliance to the recommended dietary plan ( 5 , 19 ). Our patient reacted well because we tailored a diet regimen in accordance with the above principles by combining formula nutrients with selected foods, which was more readily accepted and adhered to by the patient.…”
Section: Discussionmentioning
confidence: 99%
“…However, in the literature, late-onset neuromuscular MTPD with outcome of dietary treatment only accounted for a small portion of this subtype. A possible reason is that adult patients showed poor compliance to the recommended dietary plan ( 5 , 19 ). Our patient reacted well because we tailored a diet regimen in accordance with the above principles by combining formula nutrients with selected foods, which was more readily accepted and adhered to by the patient.…”
Section: Discussionmentioning
confidence: 99%
“…et al 12 reported peripheral polyneuropathy, rhabdomyolysis, and infantileonset hypoparathyroidism in two siblings with HADHB gene mutations. Recently, van Vliet et al 13 reported a 20-year-old woman who had axonal motor-sensory polyneuropathy of unknown origin since childhood. She presented with progressive dyspnea, and increased muscle weakness which had been preceded by an infectious disease.…”
Section: Naikimentioning
confidence: 99%
“…In some late-onset cases, the symptoms of peripheral neuropathy are similar to those of Charcot–Marie–Tooth disease (CMT) ( 4 , 5 ). Additionally, some cases are complicated by hypoparathyroidism ( 6 , 7 ).…”
Section: Introductionmentioning
confidence: 99%